Consumo de moda e representações nas telenovelas: : a construção da identidade da mulher plus size - Ankerkrone, Marcela Bezelga Francfort (2015)
This research aims to investigate the representation of the plus size women in fashion and Brazilian soap opera, as well as its reinterpretation in building the women s identity and consumer habits. The proposed research problem argues over the relationship of the plus size women with fashion and its perception of female representation in the Brazilian soap opera, exploring the understanding of the interviewees with regard to the construction of their own identities. We determined as the primary research focus the analysis of the of plus size women with the beauty standards established culturally and socially. In order to solve the research problem, we used theoretical bibliography review from authors that discuss about corporeality, such as Nízia Villaça, Tania Hoff, Erving Goffman, Mary Del Priore, among others; for communication and soap opera, we review authors like Maria Aparecida Baccega, Maria Immacolata Vassalo de Lopes, Marcia Tondato, etc; for fashion Carol Garcia, Diana Crane and Gilles Lipovetsky; for consumption Don Slater, Mary Douglas and Baron Isherwood; and with regards to identity authors like Tomaz Tadeu da Silva and Stuar Hall. The methodological approach made was the use of qualitative in-depth interviews. The survey universe consisted by women between 20 and 45 years old, residents of the city of Sao Paulo, which were engaged in remunerated activity and watch soap operas.